Analysis of Occupational Safety Risks in the PB Production Division. Sa Sri Anugerah Karawang Uses Hazard Identification, Risk Assessment, And Determining Control (Hiradc) Method - Diaz Muhamad Ilham; Annisa Maharani Suyono (Publikasi Indonesia, 2025)
Occupational Safety and Health (K3) is very important for industrial operations, including the food processing sector. However, the high rate of work accidents in the Production Division of the SA Sri Anugerah Rice Factory, with a percentage of 54% in the period 2020 to 2024, shows that there are serious problems in the implementation of K3 procedures. This research aims to identify hazards, assess risks, and determine appropriate control measures. The method used was Hazard Identification, Risk Assessment, and Determining Control (HIRADC), with data collected through interviews. The results of the study show fluctuations in accidents, starting from 15 cases in 2020 to 22 cases in 2024. The Production Division accounted for the most accidents. Occupational risks range from Low Risk to High Risk, with a high risk in the process of peeling the skin and storage of the sack that has the potential to cause serious injury. Recommended control measures include technical engineering (such as engine guards and exhaust fans), improvements to the work environment (anti-slip flooring and safe storage systems), as well as training, work rotations, and the provision of PPE (masks, eye protection, gloves, support belts). This research provides an overview of occupational safety risks and solutions to create a safe work environment.